2019
DOI: 10.3390/ani9080530
|View full text |Cite
|
Sign up to set email alerts
|

Halal Criteria Versus Conventional Slaughter Technology

Abstract: The halal meat industry is today a reality in many regions of the world, including the European Union. The main religious laws in the area of halal meat production were legislated in ancient times and may be unchangeable due to their sanctity perceived by faithful Muslims, while the modern technology used in the meat industry is constantly evolving and being updated. The objective of this study is to highlight the points of controversy between the principles of halal and the technological means currently used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 52 publications
0
30
1
4
Order By: Relevance
“…Moreover, stunning prior to bleeding during the slaughter process can greatly reduce pain perception. However, the 'halal' slaughter widely practiced in Nigeria appears yet to fully embrace stunning, particularly penetrative percussive stunning, even though some workers [62,63] have reported this stunning type able to knock out the consciousness in slaughter animals with ease. Stress due to decreased pre-slaughter welfare conditions (no housing and harsh climatic conditions) observed in this study can lower the immune status of slaughter cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, stunning prior to bleeding during the slaughter process can greatly reduce pain perception. However, the 'halal' slaughter widely practiced in Nigeria appears yet to fully embrace stunning, particularly penetrative percussive stunning, even though some workers [62,63] have reported this stunning type able to knock out the consciousness in slaughter animals with ease. Stress due to decreased pre-slaughter welfare conditions (no housing and harsh climatic conditions) observed in this study can lower the immune status of slaughter cattle.…”
Section: Discussionmentioning
confidence: 99%
“…In both halal and shechita slaughter, appropriate animal restraint is critical in maximising animal welfare, improving the quality of the meat product, maintaining adherence to slaughter rules, and safeguarding operator safety [19,20]. If animals panic due to inadequate restraint, the accuracy of the incision may be impaired [21].…”
Section: Traditional Slaughter Methodsmentioning
confidence: 99%
“…This study demonstrated that false aneurysms could form when the arteries were cut at the C1 position, but their frequency was 2.5 times lower compared to the C3 position. Therefore, neck cutting at C1 would minimise poor animal welfare outcome during slaughter without stunning (Abdullah et al., 2019).…”
Section: Assessmentmentioning
confidence: 99%